Sales Monitoring System for Vending Machine Using IoT - SIVA RAJU,; DR HUDA BIN A MAJID, (Progress in Engineering Application and Technology, 2023)
The purpose of this project is to develop a sales monitoring system for vending machines using IoT (Internet of Things) technology. The system involves the integration of a vending machine with a voltage sensor and utilizes the NodeMcu ESP32 Wi-Fi microcontroller as the interface. The objective is to enable real-time monitoring of beverage sales through a web-based application powered by Google Sheets. By implementing this project, vending machine owners can remotely monitor the sales and inventory status of beverages in their machines. The system provides updates to a Google Sheet, allowing owners to track beverage sales and determine when refills are required. This capability reduces transportation costs by optimizing refill timings, ensuring beverages are replenished only when necessary. The main goals of the project are to develop an IoT system for monitoring and managing beverages in vending machines, establish seamless integration between the IoT system and Google Sheets via cloud-based database storage, and evaluate the performance of the beverage monitoring system in a real-world environment. The NodeMcu ESP32 Wi-Fi microcontroller serves as the central component, while the Google Sheets platform enables convenient and accessible monitoring from anywhere. With the NodeMcu ESP 32 microcontroller as the core component, the system provides comprehensive sales reports for analyzing consumer behaviour and optimizing operations. By leveraging IoT technology and cloud connectivity, this sales monitoring system offers vending machine owners a valuable tool for maximizing revenue and streamlining operations. Overall, this project enhances vending machine operations by providing owners with comprehensive visibility into beverage inventory and sales data. The integration of IoT technology and Google Sheets empowers owners to make data-driven decisions, improving efficiency and profitability.